Proceeding on Management, Education and Social Science 2020
DOI: 10.31098/mess.v1i1.8
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Using Instructional Strategy Based on The Brain’s Natural Learning Systems for Special Needs Students in the Inclusive Classroom

Abstract: The problem that occurs in learning in inclusive classrooms is that teachers have not been able to design learning effectively that can accommodate the needs of all students, including students with special needs. The purpose of this study is to explore the opinions of the general teacher (GT) and special teacher (ST) about the impact of using instructional strategies based on the brain's natural learning system for special needs students (SNS) in inclusive classes. Data were collected through classroom observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 10 publications
(11 reference statements)
0
4
0
Order By: Relevance
“…Particularly for special needs, student studies found that emotional supports increase the level of satisfaction (Gunawardena & Zittle, 1997). Likewise, Rasmitadila et al (2020), depicted the importance of instructional based strategies for enhancing special need students, satisfaction with their e-learning experience. Whereas the current study is unique in checking the impact of special need students' social presence to get satisfied with the online learning experience.…”
Section: / 19mentioning
confidence: 99%
See 2 more Smart Citations
“…Particularly for special needs, student studies found that emotional supports increase the level of satisfaction (Gunawardena & Zittle, 1997). Likewise, Rasmitadila et al (2020), depicted the importance of instructional based strategies for enhancing special need students, satisfaction with their e-learning experience. Whereas the current study is unique in checking the impact of special need students' social presence to get satisfied with the online learning experience.…”
Section: / 19mentioning
confidence: 99%
“…Further, the institution and an instructor need to ensure that the content is well structured and well presented to ensure quality (Ramos-Morcillo et al, 2020). Exclusively for special needs students, the content matters a lot for developing sound understanding and engagement (Rasmitadila et al, 2020). Therefore, the content design would be of course, customized and unique based on the specific needs of the special needs students to promote a sense of community and collaboration to make the students satisfied (Caskurlu et al, 2020).…”
Section: / 19mentioning
confidence: 99%
See 1 more Smart Citation
“…Increasing participation with inclusive education providers for students and their parents requires attention to effectively managing educational resources to achieve quality education (Rasmitadia et al, 2020;Efendi et al, 2022). For this reason, effective strategies are needed in inclusive classrooms to achieve positive results for all students.…”
Section: Introductionmentioning
confidence: 99%